Delayed cognitive and psychiatric symptoms following methyl iodide and manganese poisoning: Potential for misdiagnosis. (January 2016) - Mackenzie Ross, Sarah
Abstract: This paper describes two patients who were exposed to toxic substances in the workplace, but for whom diagnosis proved difficult, particularly in case 2. Case 1 was exposed to methyl iodide and case 2 to manganese. Poisoning was characterised by delayed onset of symptoms following exposure and symptom progression after cessation of exposure. The clinical consequences of exposure to these substances include cerebellar and Parkinsonian symptoms followed by the development of cognitive impairment and the late appearance of psychiatric disturbances. Both cases were evaluated by physicians with little training in toxicology. Apart from abnormal liver function in case 1 and decreased power, coordination and proprioception in case 2, results of most routine medical investigations were normal. Both cases were referred for MRI brain scan and neuropsychological assessment. Abnormalities were noted on MRI but reported as being absent initially in case 1and of unknown significance in case 2. There was evidence of cognitive impairment in both and personality change in case 1 of sufficient severity to prevent both cases from returning to work and to impact on family life. There is no antidote to methyl iodide or manganese poisoning. Successful treatment requires early diagnosis and cessation of exposure, but neurotoxic syndromes are difficult to diagnose when a time lag exists between exposure and symptom onset and there is no biomarker of exposure. These syndromes may initially be confused with other neurodegenerative conditions, infectious processes, and psychiatric disorders. Clinician's lack of familiarity with the potential toxicity of environmental and industrial chemicals can lead to misdiagnosis and mismanagement, and this lack of recognition can lead to continued exposure. These cases highlight the importance of taking a detailed occupational history in patients who present with atypical neurological symptoms.